Hypoxia-driven heterogeneous expression of α5 integrin in glioblastoma stem cells is linked to HIF-2α - Messé, Mélissa; Bernhard, Chloé; Foppolo, Sophie; Thomas, Lionel; Marchand, Patrice; Herold-Mende, Christel; Idbaih, Ahmed; Kessler, Horst; Etienne-Selloum, Nelly; Ochoa, Charles; Tambar, Uttam K.; Elati, Mohamed; et al. (Biochimica et biophysica acta. Molecular basis of disease, 2024)
Despite numerous molecular targeted therapies tested in glioblastoma (GBM), no significant progress in patient survival has been achieved in the last 20 years in the overall population of GBM patients except with TTfield setup associated with the standard of care chemoradiotherapy. Therapy resistance is associated with target expression heterogeneity and plasticity between tumors and in tumor niches. We focused on α5 integrin implicated in aggressive GBM in preclinical and clinical samples. To address the characteristics of α5 integrin heterogeneity we started with patient data indicating that elevated levels of its mRNA are related to hypoxia pathways. We turned on glioma stem cells which are considered at the apex of tumor formation and recurrence but also as they localize in hypoxic niches. We demonstrated that α5 integrin expression is stem cell line dependent and is modulated positively by hypoxia in vitro. Importantly, heterogeneity of expression is conserved in in vivo stem cell-derived mice xenografts. In hypoxic niches, HIF-2α is preferentially implicated in α5 integrin expression which confers migratory capacity to GBM stem cells. Hence combining HIF-2α and α5 integrin inhibitors resulted in proliferation and migration impairment of α5 integrin expressing cells. Stabilization of HIF-2α is however not sufficient to control integrin α5 expression. Our results show that AHR (aryl hydrocarbon receptor) expression is inversely related to HIF-2α and α5 integrin expressions suggesting a functional competition between the two transcription factors. Collectively, data confirm the high heterogeneity of a GBM therapeutic target, its induction in hypoxic niches by HIF-2α and suggest a new way to attack molecularly defined GBM stem cells.
Online verfügbar: 21. August 2024, Artikelversion: 27. August 2024
Gesehen am 07.11.2024